2019
DOI: 10.17826/cumj.554402
|View full text |Cite
|
Sign up to set email alerts
|

Tip 2 diyabetli hastalarda tedaviye uyum ve hastalık kabulü arasındaki ilişki

Abstract: This study aimed at examining the relationship between patient acceptance of illness and adherence to treatment with type 2 diabetes mellitus. Materials and Methods: This cross-sectional, descriptive study was conducted in a state hospital in Sinop with 200 patients diagnosed with type 2 diabetes. The Patient Identification Form, Illness Acceptance Scale, and Adherence Scale to Type 2 Diabetes Mellitus Treatment were applied to collect the study data. Results: In our study, the mean score of the patients' acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
5
0
5
Order By: Relevance
“…According to the meta-analysis, compliance with DM treatment was changing between 38.5-93.1% in patients with type 2 diabetes (Krass et al, 2015), and compliance was lower in diabetic patients compared to patients with other chronic diseases (Hagerstrom, 2010). Like our study, the studies found in the literature concluded also that compliance with treatment was moderate in most of the patients with diabetes (Demirtas, 2014;Korkmaz, 2018;Ozkaptan et al, 2019;Ozonuk, 2017). These findings show that compliance with DM treatment is insufficient in many patients because of the necessity of a profound change in the lifestyle during the management of DM, which is a chronic disease.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…According to the meta-analysis, compliance with DM treatment was changing between 38.5-93.1% in patients with type 2 diabetes (Krass et al, 2015), and compliance was lower in diabetic patients compared to patients with other chronic diseases (Hagerstrom, 2010). Like our study, the studies found in the literature concluded also that compliance with treatment was moderate in most of the patients with diabetes (Demirtas, 2014;Korkmaz, 2018;Ozkaptan et al, 2019;Ozonuk, 2017). These findings show that compliance with DM treatment is insufficient in many patients because of the necessity of a profound change in the lifestyle during the management of DM, which is a chronic disease.…”
Section: Discussionsupporting
confidence: 84%
“…It has been determined that compliance with treatment increased with the increase in the educational level among patients with type 2 diabetes (Table 3). The studies in the literature showed also that compliance with treatment was increased with the educational level (Demirtas, 2014;Mogre et al, 2017;Ozkaptan et al, 2019). The educational level is an important factor for the projection of the recommendations related to compliance with treatment to behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluasi pengalaman peserta dan terapis dengan intervensi umumnya positif Sopia Marlina, Udin Rosidin, Sandra Pebrianti* Fakultas Ilmu Keperawatan Universitas Padjadjaran Bandung Jawa Barat Korespondensi Penulis: Sandra Pebrianti. Email: sandrapebrianti7@gmail.com DOI: https://doi.org/10.33024/hjk.v15i1.4093 125 5 (Kapucu, 2019) Relationship between adherence to Treatment and acceptance of illness in patients with type 2 diabetes Turki, 2019 S: 200 pasien yang didiagnosis dengan diabetes tipe 2. V: illness acceptance dan persetujuan pengobatan I: formulir pasien, skala penerimaan penyakit dan kepatuhan terhadap pengobatan diabetes mellitus tipe 2 cross-sectional, deskriptif Hasil penelitian, skor rata-rata pasien skala penerimaan adalah 24,12 ± 9,30 dan 61,5% dari pasien mendapat skor di bawah rata-rata ini.…”
Section: Metodeunclassified
“…Karakteristik tingkat pendidikan merupakan faktor penting dalam meningkatkan illness acceptance karena dengan pendidikan tinggi dapat dengan mudah menerima dan memahami informasi yang didapat serta diterapkan menjadi Sopia Marlina, Udin Rosidin, Sandra Pebrianti* Fakultas Ilmu Keperawatan Universitas Padjadjaran Bandung Jawa Barat Korespondensi Penulis: Sandra Pebrianti. Email: sandrapebrianti7@gmail.com sebuah perilaku baik (Kapucu, 2019). Dalam penelitian meskipun semua peserta menyatakan bahwa mereka telah menerima pendidikan tentang nutrisi, olahraga dan penggunaan dari perawatan yang benar tetapi mereka memiliki nilai glikemik yang tinggi.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation